Political economy of protein transition: Battles of power, framings and narratives around a false wicked problem - Béné, Christophe; Lundy, Mark (Frontiers in Sustainability, 2023)
In this paper we revisit the current debate between red meat vs. alternative protein and explore the respective contribution that those two polarized discourses claim to make in relation to the new international agenda on transforming food systems toward a more sustainable future. To complete this, we combine classical political economy analysis focusing on the access and distribution of power and economic resources amongst different groups of actors, with a more sociological approach relying on discourses analysis. The first part of the paper highlights the relevance of adopting a political economy approach to explore the centrality of factors such as incumbent actors’ powers and influence at both national and international levels. It also raises questions about the equitable redistribution of the dividends of the sector’s rapid growth between the different groups of actors and in particular the marginalization of the smallholders. We then deconstruct some of the main narratives and counter-narratives that have emerged over the last two decades around the question of protein transition and show how those different narratives have been used as ‘discursive tools’ by both the red meat and the alternative protein proponents to advance their own agendas and ignore others’. In doing so, we expose some of the unnecessary polarized or confrontational elements of the debate and suggest that the wicked nature of the problem as it appears at first sight may in fact be more the result of the framing used by particular actors, rather than the consequence of an irreconcilable tensions between diverging priorities.